(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
Mentha asiatica Boriss. in two phases received essential oils: in the phase of vegetation and flowering. The aboveground part in the phase of the growing season contains 0.10%, in the leaves - 0.13%; the phase in the aboveground part flowering contains 0.14%, in the leaves - 0.17%, and in inflorescences - 0.23% of essential oil.